2020
DOI: 10.1177/1753425920901560
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microRNA expression profiles in porcine PBMCs after LPS stimulation

Abstract: In the present study, we used microRNA (miRNA) sequencing to discover and explore the expression profiles of known and novel miRNAs in 1000 ng/ml LPS stimulated for 8 h vis-à-vis non-stimulated (i.e. control) PBMCs isolated from the blood of healthy pigs. A total of 291 known miRNAs were bio-computationally identified in porcine PBMCs, and 228 novel miRNAs (not enlisted in the swine mirBase) were identified. Among these miRNAs, ssc-miR-148a-3p, ssc-let-7g, ssc-let-7f, 3_8760, ssc-miR-26a, ssc-miR-451,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…In our recent study, we applied small RNA sequencing to investigated miRNA expression changes in porcine PBMCs in response to LPS and identified only 15 DE miRNAs. 12 Therefore, we thought LPS might have more influence on protein-coding RNA than non-coding RNA in porcine PBMCs. In addition, we found that there were no DE lncRNAs and mRNAs distributed on chromosome Y.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In our recent study, we applied small RNA sequencing to investigated miRNA expression changes in porcine PBMCs in response to LPS and identified only 15 DE miRNAs. 12 Therefore, we thought LPS might have more influence on protein-coding RNA than non-coding RNA in porcine PBMCs. In addition, we found that there were no DE lncRNAs and mRNAs distributed on chromosome Y.…”
Section: Discussionmentioning
confidence: 94%
“…The PBMCs from the blood of the Duroc × Landrace × Large White (DLW) crossbred piglets (∼15 kg, ∼8 wk old) were isolated by Ficoll-Hypaque density gradient centrifugation at 25°C. 12 The PBMCs were cultured in RPMI 1640 medium (Gibco, Australia) supplemented with 10% heat-inactivated FBS (Gibco, Australia), 2 mmol/l l -glutamine, 100 U/ml penicillin and streptomycin (Gibco) at 37°C under 5% CO 2 . LPS ( Escherichia coli serotype 026:B6, Sigma Chemical, St Louis, MO, USA) was dissolved (10 μg/ml) in saline solution.…”
Section: Methodsmentioning
confidence: 99%
“…Aberrant miRNA 152 has been reported in placental tissues in pregnancy complications [ 40 ]. miRNA 152 is also reported to regulate the innate immune response and antigen-presenting capacity of dendritic cells [ 41 ] and altered in circulating mononuclear cells stimulated by LPS [ 42 ]. It is plausible that the shared DEmiRNAs mediate deleterious periodontitis-associated endotoxin tolerance and inflammatory pathways active at the maternal-fetal interface, which is known to contribute to preeclampsia [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, more transcripts of the dysregulated mRNA or lncRNAs were observed to be up-regulated after LPS stimulation in human and porcine PBMCs. In our recent study, we had investigated the changes in miRNA expression in porcine PBMCs after in vitro stimulation with LPS and identi ed only 15 DE miRNA in response to LPS by using small RNA sequencing [12]. Therefore, we thought LPS stimulation might have more in uence on protein coding RNA more than non-coding RNA in PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…The PBMCs from the blood of the Duroc × Landrace × Large White (DLW) crossbred piglets (~ 15 kg, ~ 8week-old) were isolated by Ficoll-Hypaque density gradient centrifugation at room temperature [12]. The PBMCs were cultured in RPMI 1640 medium (Gibco, Australia) supplemented with 10% heat-inactivated FBS (Gibco, Australia), 2 mmol/L L-glutamine, 100 U/mL penicillin and streptomycin (Gibco) at 37 °C under 5% CO 2 .…”
Section: Cell Isolation Culture and Stimulationmentioning
confidence: 99%